ANALISIS TINGKAT KEPUASAN PENGGUNA GERBONG KHUSUS WANITA KERETA REL LISTRIK COMMUTERLINE RANGKASBITUNG - Sahira Mardarena; R. Slamet Santoso (Journal of Management and Public Policy, 2026)
Metropolitan areas such as Jakarta have high levels of vehicle use, which causes traffic congestion. The government provides public transportation such as the KRL, operated by KAI Commuter, to facilitate public mobility. However, this service still receives complaints, especially from female passengers on women-only carriages. On the Rangkasbitung Commuterline, the number of women-only carriages is still limited, so some passengers use the general carriages. This situation has the potential to cause discomfort and the risk of harassment, so the provision of women-only carriages and a complaint system needs attention. The study aims to determine the relationship between Service Quality (X1) and User Satisfaction (Y), the relationship between Complaint Handling (X2) and User Satisfaction (Y), and the relationship between Service Quality (X1) and Complaint Handling (X2) on User Satisfaction (Y) among passengers in women-only carriages, with the theory matrix as the focus of the study due to its higher density compared to other routes. The method used an explanatory quantitative approach with data collection in the form of questionnaires, documentation, and interviews based on proportional random sampling of 100 female carriage users spread across stations on the Rangkasbitung Commuterline. Data analysis included Spearman's rho validity, Cronbach's alpha reliability, Kendall Tau (τ) correlation, Kendall Concordance (W), and Coefficient of Determination (R2). The results showed a positive and significant relationship between Service Quality (X1) and User Satisfaction (Y) of 0.341 and a Coefficient of Determination with a contribution of 37.6%. The correlation of other variables shows a positive and significant relationship between Complaint Handling (X2) and User Satisfaction (Y) of 0.238 and the Coefficient of Determination with a contribution of 24.9%. Stimulatingly, there is a positive relationship between Service Quality (X1) and Complaint Handling (X2) with User Satisfaction (Y) of 0.434 and a Coefficient of Determination of 37.7%.